Caribbean Report 17-01-1997 - Orr, Carol (anchor); McGee, Sean (interviewee); Timothy, Julius (interviewee); Fraser, Tony (correspondent); Headley, Trevor (interviewee); Richards, Ken (correspondent) (The British Broadcasting Corporation, 1997)
Plans by the Dominican government to sell 73% of the state run company DOMLEC has stirred accusations of a cover up and sell-out by groups opposed to the sale. The plan is to sell the shares to the Commonwealth Development Corporation. Next, protest in southern of Trinidad by oil workers is discussed. The protest has caused the South Western Peninsula of Trinidad to be blocked off from traffic. The following states that after years, two persons face trial for the killing of an Acetic Jew in Brooklyn. One Jamaica born lawyer says the move is political. The following segment discusses a move to give British police legal powers to enter, search and bug the homes of UK citizens is running into opposition. Civil liberty groups believe that the bill if passed will erode individual privacy and overturn centuries of traditional rights. In the following segment, the Canadian Foreign Affairs Minister Lloyd Axworthy may meet with President Fidel Castro during a visit to Cuba next week. His trip highlights Canada’s desire to dialogue with Cuba on matters of mutual interest. Finally, an evicted Vincentian woman, Princess Caesar, wins almost US two million dollars in a New York lottery.
1. Headlines (00:00-00:30)
2. Proposed foreign sales of Dominica's Electricity Company stirs accusations of a sell-out. Interviews by Sean McGee, Commonwealth Development Corporate Manager and Julius Timothy (00:31-06:37)
3. Demonstrations in the South Western part of Trinidad. Tony Fraser reports from Port of Spain (06:38-07:58)
4. After four years two persons face trial for the killing of Acetic Jew in Brooklyn. Interview with Trevor Headley, Attorney (07:59-11:17)
Keywords: Dominican Electricity Company.; Commonweatlh Development Corporation.; Demonstrations -- Trinidad and Tobago.; Oil workers -- Trinidad and Tobago.; Crown Heights Community - Brooklyn.; Acetic Jew.; Police -- Britain -- Extensive powers.; Civil Liberty Groups.; Canada -- Foreign relations.; Lottery -- New York.